Local Government Financial Performance Reviewed from Financial Ratios and Indexes - Nella Rahanratat (Program Studi Akuntansi Unimuda Sorong, 2024)
This research aims to analyze the financial performance of the Ambon City regional government in terms of financial ratios in implementing regional autonomy. This research is a descriptive qualitative research type. Using documentation study data collection techniques or by tracing which is done by collecting secondary data, namely regional government financial report data for 2012 - 2015 from related agencies. The data analysis technique used is the descriptive analysis technique to assess financial performance, namely the regional independence ratio, effectiveness ratio, regional financial activity/harmony ratio and regional financial growth ratio, assessing financial capability using the degree of fiscal autonomy ratio and routine capability index. The research results found that the Regional Financial Independence Ratio (RKKD) of Ambon City during the three year observation period from 2013 to 2015 was on a scale of 0% - 25%, which means it was classified as